Band gap and defect engineering of bismuth vanadate using La, Ce, Zr dopants to obtain a photoelectrochemical system for ultra-sensitive detection of glucose in blood serum. Issue 7 (24th January 2023) - Prakash, Jyoti; Nechiyil, Divya; Ali, Kawsar; Sharma, Sandeep K.; Dey, Anusree; Uppal, Sheetal; Arya, Ashok
Abstract : Bismuth vanadate (BiVO4 ) is a promising photoactive material for the design of photoelectrochemical (PEC) analytical devices for the non-enzymatic detection of glucose. Abstract : Bismuth vanadate (BiVO4 ) is a promising photoactive material for the design of photoelectrochemical (PEC) analytical devices for the non-enzymatic detection of glucose. In this work, un-doped and La/Ce/Zr doped BiVO4 photo anodes were developed by spray pyrolysis coating to generate unique 2D hierarchical architectures using the facile ultrasonic spray coating technique without any complex pre or post-treatment. The influence of different dopants on the morphology and photoelectrochemical activity of BiVO4 coatings was investigated. X-ray diffraction, scanning electron microscopy, UV-vis optical absorbance, and positron annihilation techniques were used to evaluate the structure, defects, and optical properties of BiVO4 films. DFT simulation confirmed the Zr doping induced band gap reduction in the BiVO4 lattice. The Zr doping on the Bi site in BiVO4 lattice provided significantly low Bi and V-based defect density and a higher bulk diffusion length of charge pairs (4 times that of pristine) as well as charge transfer efficiency and this led to the foremost photocurrent for water splitting. The Zr-doped BiVO4 photo anode showed remarkable sensitivity in glucose sensing. The sensitivity and limit of detection of the Zr-doped BiVO4 PEC device towards glucose were 0.14 mA cm −2 mM −1 and 1.22 μM, respectively, in the concentration range of 1–7 mM. The system showed sensitive detection of glucose in blood serum. This is the first time that a 2D morphology electrode design consisting of Zr-doped BiVO4, which leads to exceptionally high sensitivity for glucose sensing, has been reported.